2022
DOI: 10.1038/s41598-022-06221-8
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent plasma in the treatment of moderate to severe COVID-19 pneumonia: a randomized controlled trial (PROTECT-Patient Trial)

Abstract: There is a need for effective therapy for COVID-19 pneumonia. Convalescent plasma has antiviral activity and early observational studies suggested benefit in reducing COVID-19 severity. We investigated the safety and efficacy of convalescent plasma in hospitalized patients with COVID-19 in a population with a high HIV prevalence and where few therapeutic options were available. We performed a double-blinded, multicenter, randomized controlled trial in one private and three public sector hospitals in South Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…A total of 19 studies [ 17 , 19 , 22 , 41 , 43 , 44 , 47 49 , 51 , 52 , 57 , 60 , 63 , 68 , 70 , 73 , 77 , 81 ] ( N = 26,912) reported the incidence of progression to invasive mechanical ventilation and/or ECMO and were included in the NMA. No intervention was associated with significant reductions in the odds of invasive mechanical ventilation/ECMO (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 19 studies [ 17 , 19 , 22 , 41 , 43 , 44 , 47 49 , 51 , 52 , 57 , 60 , 63 , 68 , 70 , 73 , 77 , 81 ] ( N = 26,912) reported the incidence of progression to invasive mechanical ventilation and/or ECMO and were included in the NMA. No intervention was associated with significant reductions in the odds of invasive mechanical ventilation/ECMO (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among all the included studies, 4 studies ( 24 , 28 , 34 , 48 ) were preprinted and 28 studies ( 16 – 18 , 25 27 , 29 33 , 35 – 47 , 49 52 ) were published in peer-reviewed journals. 10 studies ( 24 , 26 , 31 , 38 , 41 , 43 , 44 , 46 , 50 , 51 ) were double-blind RCTs with placebo and 22 studies ( 16 – 18 , 25 , 27 30 , 32 37 , 39 , 40 , 42 , 45 , 47 49 , 52 ) were designed as open-label trials. All trials included patients with confirmed Covid-19 except for the RECOVERY trial ( 35 ), which included both suspected and confirmed COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…8 studies ( 26 , 35 , 38 , 41 , 43 , 44 , 46 , 50 ) were regarded as low risk of bias, and 16 studies ( 16 – 18 , 25 , 27 , 29 , 30 , 32 , 37 , 39 , 40 , 42 , 45 , 47 , 49 , 52 ) contained potential performance bias for the open-label design. 4 studies were considered as containing potential bias due to early termination ( 31 , 33 , 36 , 51 ). Notably, although no high risks of bias in D1-D5, 4 studies ( 24 , 28 , 34 , 48 ) were classified as high risk for pre-printed and lack of peer review.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, results of a randomized clinical trial of CCP treatment in hospitalized COVID‐19 patients with moderate to severe disease showed no clinical improvement relative to the placebo, providing support against the use of CCP treatment for COVID‐19 pneumonia (van den Berg et al., 2022 ). The results from a randomized controlled, open‐label, platform trial also showed no improvement in survival or other clinical outcomes in hospitalized COVID‐19 patients treated with high‐titer CP (RECOVERY Collaborative Group, 2021a ).…”
Section: Cp To Treat Viral Conditions Including Covid‐19 Diseasementioning
confidence: 99%
“…The results from a randomized controlled, open‐label, platform trial also showed no improvement in survival or other clinical outcomes in hospitalized COVID‐19 patients treated with high‐titer CP (RECOVERY Collaborative Group, 2021a ). Indeed, CCP can be used for either prophylaxis of infection or treatment of disease (Casadevall & Pirofski, 2020 ), however as highlighted above (Duan et al., 2020 ; Shen et al., 2020 ; van den Berg et al., 2022 ), and by other experts in the field (Dzik, 2020 ), it is important to conduct additional studies and randomized controlled investigations to confirm the effectiveness and safety of using CCP in all types of COVID‐19 hospitalized patients, particularly for those at risk of progressing to critical state. For example, Allahyari et al.…”
Section: Cp To Treat Viral Conditions Including Covid‐19 Diseasementioning
confidence: 99%